A study of organizational versus individual needs related to recruitment, deployment and promotion of doctors working in the government health system in Odisha state, India. Issue 1 (December 2016) - Kadam, Shridhar; Nallala, Srinivas; Zodpey, Sanjay; Pati, Sanghamitra; Hussain, Mohammad; Chauhan, Abhimanyu; Das, Sovesh; Martineau, Tim
Abstract Background An effective health workforce is essential for achieving health-related new Sustainable Development Goals. Odisha, one of the states in India with low health indicators, faces challenges in recruiting and retaining health staff in the public sector, especially doctors. Recruitment, deployment and career progression play an important role in attracting and retaining doctors. We examined the policies on recruitment, deployment and promotion for doctors in the state and how these policies were perceived to be implemented. Methods We undertook document review and four key informant interviews with senior state-level officials to delineate the policies for recruitment, deployment and promotion. We conducted 90 in-depth interviews, 86 with doctors from six districts and four at the state level to explore the perceptions of doctors about these policies. Results Despite the efforts by the Government of Odisha through regular recruitments, a quarter of the posts of doctors was vacant across all institutional levels in the state. The majority of doctors interviewed were unaware of existing government rules for placement, transfer and promotion. In addition, there were no explicit rules followed in placement and transfer. More than half (57%) of the doctors interviewed from well-accessible areas had never worked in the identified hard-to-reach areas in spite of having regulatory and incentive mechanisms. The average length of service before the first promotion was 26 (±3.5) years. The doctors expressed satisfaction with the recruitment process. They stated concerns over delayed first promotion, non-transparent deployment policies and ineffective incentive system. Almost all doctors suggested having time-bound and transparent policies. Conclusions Adequate and appropriate deployment of doctors is a challenge for the government as it has to align the individual aspirations of employees with organizational needs. Explicit rules for human resource management coupled with transparency in implementation can improve governance and build trust among doctors which would encourage them to work in the public sector.